Study on the Effect of Chemical Plant Growth Regulators on Corn Growth in Indramayu, West Java, Indonesia: Studi Pengaruh Pemberian Zat Pengatur Tumbuh Kimia terhadap Pertumbuhan Jagung di Indramayu Jawa Barat, Indonesia - Khaerul Muttaqien (Institute of Educational, Research, and Community Service, 2023)
This research aims to investigate the influence of applying chemical plant growth regulators on corn growth in the Indramayu region, West Java. The study involves the use of several types of chemical plant growth regulators, namely auxin, cytokinin, gibberellin, and abscisic acid. The research was conducted using a randomized block design, repeated three times to obtain reliable data. Several parameters of corn growth, such as plant height, leaf count, leaf area, root length, and plant biomass, were periodically measured during the growth period. The data analysis results show that the application of chemical plant growth regulators significantly affects the growth and development of corn plants. Each type of chemical plant growth regulator has a distinct effect on plant growth. Auxin enhances root and vegetative growth, cytokinin boosts vegetative growth, gibberellin increases plant height and seed count, while abscisic acid improves drought tolerance. Although chemical plant growth regulators provide benefits for corn growth, it is essential to carefully consider the dosage and timing of application to avoid negative effects on plant growth. The results of this study provide a basis for farmers and agricultural practitioners to understand the appropriate and optimal use of chemical plant growth regulators for corn plants